(3OjhGf GHf MLQ GdYSbdGfis - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3TeS GdOjf GdSNGhi GdeUfa GdeYQha s)
(3ChdgG (B:s
(3bGd TjNfG GdEeGe Yde GdYdeGA GdCYdGe TjN GdESdGe MGaX eUQ hGdTGe dSGf GdYQH hMLI GdCOH ghi ajg GdedGSI cGdghGA adG jWeY dfGOi ai GfWaGA s
(3BNQgG (B:s
(3Hi MH SeQG TaJgG HGdbHd XejkG hdMXgG GdSge KGHJ ai GdMTi BNQ GdOjhGf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs